Area-based Development for Sustainability: the Case of Kok Nong Na Model - Chaisrisawatsuk, Santi; Chaisrisawatsuk , Wisit (Journal of Applied Economics and Management Strategy [eISSN 2985-1408], 2024)
Area-based approach has gained more appreciation over time in Thailand development process. Together with the application of Sufficiency Economy Philosophy (SEP) and the New Agriculture Theory established by many Royal initiatives as experimental showcases. It highlights greater success and a better suitable approach in reaching out for poor farmers in the rural area. Highlight on agriculture diversity, better utilization and management of farm essential resources, and community knowledge collaboration (much more on bottom-up approach), KNN model practice has shown in this study to be an interesting alternative for social and economic development for developing country with inequality gap. Some initial investment is required for storage of water for year-round farming and cultivation. The practice fits perfectly with Biodiversity, Circular, and Green (BCG) economy where various types of plants, trees, fishery, and cattle are combined in farming activities based on each individual farmer’s interest and specialization. Residuals from one farming activity are used to further enhance other farming activity productivity, and improving land fertility. Diversity agriculture reduces the need for pesticide as opposed to monocropping. The farming approached as mentioned above has been proven to be benefited and in line with large scale farmers, where the advantages of economies of scale and diversity of productions can easily be combined. Unfortunately, the same principle cannot be applied to smaller size farmers who appear to be dominated in Thai agriculture sector. Therefore, the objective of this study is to come up with some concrete assessment of possible success of smaller farmers to be successful in their transition into KNN model practice. KNN model can be adopted as another alternative approach for agriculture sector and area-based development strategy in Thailand. A hypothetical household (small size) was set up by extracting information from questionnaires and surveys with KNN model farmers across country and benefit-cost analysis method was used for the feasibility analysis. The study shows that, financially, KNN model has proven to be feasible for farmer with small, medium, and large size of land (data from our surveys indicates that most larger land pot farmers practicing KNN model are successful farmers). A sizable amount of funding is needed as an initial investment and funding also required for later stages to maintain fertility of the plot even though part of these needs can be fulfilled by some of the short-term income generated. The process might take roughly about 4-5 years for farmer to be successful and stabilized by which they earn sustainable annual income above the self-sufficiency level. Findings from the study reaffirm that KNN model can be an alternative approach for rural community development, and it builds on farmer’s specialization toward sustainability particularly for small farmers who potentially can be left behind in the traditional development process.